2017
DOI: 10.1051/matecconf/201713707002
|View full text |Cite
|
Sign up to set email alerts
|

The study of postural workload in assembly of furniture upholstery

Abstract: Abstract. The productivity of the workers is affected by the Work-related Musculoskeletal Disorders (WRMSDs) which common cause of health problems, sick leave and it can result in decreased quality of work and increased absenteeism. The objective of this study is to evaluate and investigate the postural workload of sewing machine operators in the assembly of upholstery in furniture factory by using the Ovako Working Posture Analysing System (OWAS) with sampling. The results indicated that posture code 2111 (ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It makes an important contribution to the design and assessment of tasks, jobs, products, work environments, and organizational systems so that they meet employees' needs, capabilities, and limitations (IEA, 2023). Er-gonomics is also the science of adapting workplaces, machines, and devices to humans to ensure safety and optimal efficiency so as not to force employees to adapt to non-ergonomic workstations and tasks, which may hurt their health and workplace well-being (Lasota & Hankiewicz, 2017b). Therefore, machines, tools, workplaces, and work environments must be best adapted to human capabilities and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It makes an important contribution to the design and assessment of tasks, jobs, products, work environments, and organizational systems so that they meet employees' needs, capabilities, and limitations (IEA, 2023). Er-gonomics is also the science of adapting workplaces, machines, and devices to humans to ensure safety and optimal efficiency so as not to force employees to adapt to non-ergonomic workstations and tasks, which may hurt their health and workplace well-being (Lasota & Hankiewicz, 2017b). Therefore, machines, tools, workplaces, and work environments must be best adapted to human capabilities and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in South America, the First National Survey of Employment, Work, Health and Quality of Life Conditions was carried out in the country of Chile, which showed that 2 out of 10 working people suffer from MSDs [4]. A study carried out in Poland shows that there are characteristic postures in the production of upholstery and repetitive movements that affect the spine, arm movements below the shoulder joint and constant rotation of the body with large parts, which has repercussions on health problems, absenteeism, and low quality of work [5].…”
Section: Introductionmentioning
confidence: 99%
“…The productivity of workers is affected by musculoskeletal disorders that are generally related to work [5]. Such is so, that their research was based on analyzing the postural workload of sewing machine operators for the assembly of an upholstery shop in a furniture factory.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers widely use risk assessment methods to evaluate jobs, health outcomes and risk to WRMSDs of occupational groups in the production and assembly systems [8,9,11,27,34,35]. However, many industrial jobs are multi-task in nature [36] and there are multipurpose workstations.…”
Section: Introductionmentioning
confidence: 99%